A brief overview of the ACEP project: Ecosystem Processes in the KwaZulu-Natal Bight§. (1st June 2016) - Fennessy, ST; Roberts, MJ; Paterson, AW
Abstract : This introductory paper lays the basis for this supplementary issue by briefly presenting the state of knowledge on the KwaZulu-Natal (KZN) Bight at the start of this multi-disciplinary, multi-institutional, ship-based research project that ran from 2009 to 2013. The rationale and aims of the project are also described. The project was a major component of the South African Department of Science and Technology's African Coelacanth Ecosystem Programme (ACEP), which has been prominent in supporting research on the east coast of South Africa and the wider South-West Indian Ocean. Pivotal to this was the RS Algoa, which was made available for two 30-day surveys (winter and summer) in the KZN Bight by the Department of Environmental Affairs. Although some aspects of the bight ecology are known, much of the research is dated and fragmented, and required refreshing and consolidation in order to produce a platform upon which the understanding of the region's ecosystem functioning could be established. Much of the oceanographic knowledge is also dated, with no dedicated surveys and significant measurements undertaken since 1989. The overarching theme of the KZN Bight project was to examine the relative importance of sources of nutrients to the central KZN coast and how these are taken up and recycled in the ecosystem, and to describe aspects of the benthic biodiversity, which is poorly described in much of this region. An ambitious project, its accessibility to a ship-based research platform and the diverse scientific skills of the participating scientists allowed considerable success, as reflected in the papers that follow.